A striking example of developmental bias in an evolutionary process: The "domestication syndrome". Issue 1 (23rd September 2019) - Wilkins, Adam S.
Abstract: The question of whether "developmental bias" can influence evolution is still controversial, despite much circumstantial evidence and a good theoretical argument. Here, I will argue that the domestication of mammalian species, which took place independently more than two dozen times, provides a particularly convincing example of developmental bias in evolution. The singular finding that underlies this claim is the repeated occurrence in domesticated mammals of a set of distinctive traits, none of which were deliberately selected. This phenomenon has been termed "the domestication syndrome". In this article, I will: (a) describe the properties of the domestication syndrome; (b) show how it can be explained in terms of the operation of a specific genetic regulatory network, that which governs neural crest cell development; and (c) discuss Dmitry Belyaev's idea of "destabilizing selection, " which holds that selecting for a new behavior often entails neuroendocrine alterations that alter many aspects of development. Finally, I will argue for the potential general significance of such destabilizing selection, in combination with developmental bias, in animal evolution. Abstract : The two pictures below illustrate the pigmentation aspects of the "domestication syndrome, " an illustration of the operation of developmental bias, in two lines of silver foxes selected for opposite behaviors, aggressiveness, and tameness Research Highlights: This paper argues that the domestication of animals illustrates developmental bias in evolution, and explains it in terms of mutational alterations in the neural crest cell genetic regulatory network. The phenomenon is discussed further in terms of the idea of "destabilizing selection" and how that can be understood today.